Study on the Nitration Reaction of N,N-diphenylamine Compounds and Its Characterization as Organic Light Emitting Diode (OLED) Material - Haryanto
Organic Light Emitting Diode (OLED) is one of the developing technologies utilizing organic compounds, especially aromatic compounds which have a lot of conjugating bonds. This field is becoming more interesting because utilizing organic compounds for emissive layer of OLED has some advantages compared to inorganic compounds. Therefore, the study on the transformation of N,N- diphenylamine (DPA) compounds to search for potential compounds that can be utilized as precursor of OLED material. In this research, DPA transformation reactions have been done through nitration reaction utilizing conventional and Microwave Assisted Organic Synthesis (MAOS) method. Various reactions have been performed at 30-45 oC, 15-240 minutes, and the power of the microwave reactor is 400 W. The Thin Layer Chromatography (TLC) test using n- hexane:ethyl acetate = 7:3 (v/v) shows that the product Rf value is 0,34. The nitration reaction product of N,N-diphenylamine is characterized with Fourier- Transform Infrared (FT-IR), UV-Vis, fluorescence, and Nuclear Magnetic Resonance (NMR) spectroscopy. The FT-IR spectrum of nitration product shows unique absorption in these wavenumbers, 1306.33 cm-1 (aromatic nitro), 1597 cm-1 (aromatic nitroso); 1508.27 cm-1 (aromatic N-H); dan 2933 cm-1 (aromatic C-H). The 1H NMR spectrum (500 MHz, CDCl3) of nitration product of DPA shows seven chemical shift signals of protons at the aromatic compound region (? = 7.76- 9.18 ppm). In addition, the maximum longwave absoprtion of UV-Vis spectrum for the nitration product in acetone is 406 nm. For the emission spectrum, the product emits light at 413 and 498 nm. Based on the characterisation results, the nitration reaction of N,N-diphenylamine has been successfully performed. The product is also potential to be used as OLED material because its ability to emit light in the visible area.